THE IMMUNITY OF HEADS OF STATE AND THE APPROACH OF INTERNATIONAL AND DOMESTIC COURTS IN ITS APPLICATION - Ashkan Famil Modaberan, Masoud Vazini (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
When the heads of state in the past centuries invoked absolute immunity due to the independence and equal sovereignty of states as well as the power they enjoyed as a result of their dignity and position. The current orientation of the international legal system, as well as the approach of the United Nations and its organs, is more in the direction of preserving and protecting humanity and human rights and towards the formation of customary rules in the denial of criminal immunity Heads of state are evolving at the time of large-scale international crimes. This change can be seen in the statutes of the courts of Nuremberg, Tokyo, the former Yugoslavia, Rwanda, the Special Court of Sierra Leone, and the statute of the International Criminal Court. In addition, the current practice of international courts and, to some extent, national courts, clearly indicates that the era of absolute immunity of heads of state is over. In this regard, this article examines and explains this issue.